2021
DOI: 10.1242/jeb.242613
|View full text |Cite
|
Sign up to set email alerts
|

Cubam receptor-mediated endocytosis in hindgut-derived pseudoplacenta of a viviparous teleost Xenotoca eiseni

Abstract: Nutrient transfer from mother to the embryo is essential for reproduction in viviparous animals. In the viviparous teleost Xenotoca eiseni belonging to the family Goodeidae, the intraovarian embryo intakes the maternal component secreted into the ovarian fluid via the trophotaenia. Our previous study reported that the epithelial layer cells of the trophotaenia incorporate a maternal protein via vesicle trafficking. However, the molecules responsible for the absorption were still elusive. Here, we focused on Cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Endocytosis-mediated intracellular vesicles in cells were visualized by immunohistochemistry against cubilin, an endocytic receptor expressed in trophotaenia (Fig. 1B) [19]. To trace Vtg absorption, embryos were extracted from pregnant female fish and incubated in PBS containing Vtg-FITC for 1 h. In the case of clathrin inhibition, embryos were exposed to Pitstop-2 for 30 min prior to Vtg addition (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Endocytosis-mediated intracellular vesicles in cells were visualized by immunohistochemistry against cubilin, an endocytic receptor expressed in trophotaenia (Fig. 1B) [19]. To trace Vtg absorption, embryos were extracted from pregnant female fish and incubated in PBS containing Vtg-FITC for 1 h. In the case of clathrin inhibition, embryos were exposed to Pitstop-2 for 30 min prior to Vtg addition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that trophotaenia in intraovarian embryos possesses cathepsin L-dependent protease activity [19]. This activity may be related to the degradation of maternal proteins, including Vtg.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations